Asdzáán Náhodidáhí (Lady Picker-Up) at Fajada Butte: Astronomy, Landscape, and the Basketmaker III Origins of Chacoan Ceremonialism. Issue 3 (3rd July 2021) - Weiner, Robert S.; Kelley, Klara B.
Abstract : In this paper, we combine evidence from archaeology, landscape, astronomy, and Indigenous oral traditions to propose that Chaco Canyon was established as a regionally influential sun-moon-rain shrine beginning in the Basketmaker III period. We review the Basketmaker III archaeological record of Chaco Canyon with emphasis on Shábik'e'eshchί (29 SJ 1659), Woodpecker (29 SJ 423), and Coyote Point (29 SJ 299), a site near Fajada Butte. We suggest Shábik'e'eshchί and Woodpecker were specifically positioned to provide views of the winter solstice sunrise in alignment with Chaco Canyon's trajectory, which, together with the presence of Fajada Butte and Chaco's position in the center of the San Juan Basin, combined to establish the canyon as a unique sacred locale. We also present narratives from the Diné (Navajo) Waterway (Tóyeejí) and Navajo Windway (Diné Biníłch'ijí) Ceremonies that emphasize the importance of Fajada Butte, solar-lunar astronomy, and rainmaking in Chacoan history to support this scenario.